2019
DOI: 10.1590/2175-8239-jbn-2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Reversible posterior encephalopathy syndrome in a 10-year-old child

Abstract: Introduction: The posterior reversible encephalopathy (PRES) syndrome encompasses a set of clinical-radiological findings associated with severe systemic arterial hypertension. This case report proposes to discuss the identification, diagnosis, and management of PRES in the pediatric population. Case presentation: Female patient, 10 years old, admitted to the emergency room with complaint of oliguria and generalized edema. At the initial physical exam, the only alteration present was anasarca. The diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Therefore, according to this theory, there needs to be a sudden elevation in systemic blood pressure for PRES to occur. The second theory suggests that cytotoxic drugs, including chemotherapy agents used in our case report, can induce PRES through direct cytotoxic effects on the cerebrovascular endothelium, leading to the breakdown of the blood-brain barrier and vasogenic edema [5][6][7][8][9]. Our patient developed PRES, likely due to a combination of factors, including significant hypertension and exposure to induction chemotherapy.…”
Section: Discussionmentioning
confidence: 76%
“…Therefore, according to this theory, there needs to be a sudden elevation in systemic blood pressure for PRES to occur. The second theory suggests that cytotoxic drugs, including chemotherapy agents used in our case report, can induce PRES through direct cytotoxic effects on the cerebrovascular endothelium, leading to the breakdown of the blood-brain barrier and vasogenic edema [5][6][7][8][9]. Our patient developed PRES, likely due to a combination of factors, including significant hypertension and exposure to induction chemotherapy.…”
Section: Discussionmentioning
confidence: 76%
“…2 It can also result from the failure of the cerebrovascular auto-regulation mechanisms due to sudden elevations in blood pressure and secondary hypertension in children is commonly related to renal changes, suggesting that these are the main etiologies of PRES. 8 Ishikura et al showed that PRES may occur during moderate to severe nephrotic state in most of the paediatric patients. 4 Several additive factors predispose to the development of PRES in these patients, namely low serum albumin level, generalised edema, increase in vascular permeability, unstable fluid status and renal insufficiency along with child receiving immunosuppressive drugs like cyclosporin.…”
Section: Discussionmentioning
confidence: 99%